TEACHING ENGLISH IN HIGHER EDUCATION: MODERN APPROACHES AND CHALLENGES - Kosimova Shakhnoza Sharof kizi (International Journal of Literature and Language Studies, 2026)
The teaching of English in higher education has become increasingly important due to globalization, international academic cooperation, and the growing demand for English-language proficiency in the labor market. Universities are expected to prepare students not only with disciplinary knowledge but also with effective communication skills in English. This study examines modern approaches to teaching English in higher education, including communicative language teaching, technology-enhanced learning, task-based instruction, and student-centered methodologies. The paper also explores the challenges faced by educators and learners, such as limited resources, varying proficiency levels, and insufficient opportunities for authentic language practice. The findings suggest that integrating innovative teaching methods and digital technologies can significantly improve students’ language competence and engagement. Furthermore, continuous professional development for teachers and institutional support are essential for successful English language instruction in higher education settings.